The Santa Clara Ethics Scale - Plante, Thomas G.; McCreadie, Anna (2019)
Ethics and ethical decision-making are important for well-functioning communities and societies, including college campuses. Yet, there are very few high quality, cost-effective, relevant, and easy-to-use assessment instruments currently available. This paper introduces the new Santa Clara Ethics Scale, a very brief no-cost questionnaire assessing general ethics. The 10-item scale was administered to 200 university students along with several other measures to assess convergent and divergent validity. Information regarding the validity and reliability of the scale along with test utility is presented. Implications for future research and use are discussed as well.
Keywords: Assessment; College; Ethics; Morality